2019
DOI: 10.1016/j.envres.2019.03.068
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of model estimates from an intra-city land use regression model with a national satellite-LUR and a regional Bayesian Maximum Entropy model, in estimating NO2 for a birth cohort in Sydney, Australia

Abstract: Comparison of model estimates from an intra-city land use regression model with a national satellite-LUR and a regional Bayesian Maximum Entropy model, in estimating NO 2 for a birth cohort in Sydney, Australia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 55 publications
1
23
0
1
Order By: Relevance
“…Although Sydney's most extreme pollution events are often associated with fires and dust storms (e.g., [28,[50][51][52]), studies analysing the sources of PM 2.5 and NO X in NSW concluded that motor vehicle exhaust was the largest contributor to total NO X [53] and the largest anthropogenic contributor to total PM 2.5 [54]. Power stations are also implicated as a major source of atmospheric fine particles [18].…”
Section: Major Anthropogenic Sources Of Air Pollutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Sydney's most extreme pollution events are often associated with fires and dust storms (e.g., [28,[50][51][52]), studies analysing the sources of PM 2.5 and NO X in NSW concluded that motor vehicle exhaust was the largest contributor to total NO X [53] and the largest anthropogenic contributor to total PM 2.5 [54]. Power stations are also implicated as a major source of atmospheric fine particles [18].…”
Section: Major Anthropogenic Sources Of Air Pollutionmentioning
confidence: 99%
“…Vehicle-related pollution levels have high spatial variability and are influenced by many factors, including wind speed, traffic density, and distance from main roads [55]. Many studies have shown that pollution levels decrease rapidly with distance from major roads [53,[55][56][57][58][59][60][61]. There is now widespread evidence of the adverse health effects associated with exposure to traffic-related air pollution [62][63][64], including studies finding associations between health risks, such as the increased risk of asthma in children living closer to major roads [65].…”
Section: Major Anthropogenic Sources Of Air Pollutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is human activity in these non-urban districts, it is much less intensive than that in urban areas. LUR modeling predicts air pollutant concentrations based on surrounding land use and environmental properties [24][25][26]38,39]. To develop this model, we used spatialized environmental databases as predictor variables.…”
Section: Prediction Of No 2 Concentrations By Administrative Unit Usimentioning
confidence: 99%
“…Based on this data, an accurate NO 2 concentration map for administrative units was constructed, and seasonal concentrations were predicted using land use regression analysis. The LUR model is a statistical method that is widely used for analyzing the characteristics of air pollutant concentrations, because it has the advantage of being able to grasp the environmental influence on the NO 2 concentration spatially [24][25][26].…”
Section: Introductionmentioning
confidence: 99%